اسلامی تصوف میں مختلف نظریات کی آمیزش اور عصر حاضر میں صوفیانہ اندازکاتجزیاتی مطالعہ: Analytical study of fusion of different ideologies in Islamic Sufism and Sufi styles in contemporary times (Khairulummah, 2022)
Regarding Sufism in Islamic history, we find two groups, firstly, Ahle Sunnah Sufis, secondly, the Esoteric, in Islamic history, the Esoteric always tried to emerge under the guise of Sufism.Sufism has passed through different periods like other arts such as the science of interpretation, the science of hadith, the science of jurisprudence, the science of history, etc. Just like in other fields, there were people who harmed their respective fields, similarly in Sufism, we see esoteric and Mu'tazili interpretations, themes are created, and divergent opinions are seen in jurisprudential materials. Historical debates, especially debates, show immoderations. There are similar issues with regard to Sufism, but here our purpose is not to discuss the art of Sufism, but to discuss the types of Sufism that have arisen in modern times. .Sufism is specific form of Islamic mysticism that lays emphasis on introspection & spiritual closeness with Allah Almighty.  Sufism considers the ultimate reality and can only realized. It Shariah on the hearts of those who feel it. In Islamic terminology inner knowledge is called Sufism and the person who is called sufi. Sufism is also ornamented with modern knowledge. Every institution imports know way of but difference ties on their way of teaching same like every Sufis aim & object is to introduce speared reality of Islam but difference ties in their way of preaching. In this article different style of Sufism will be discussed. In Sufism some Sufis speared Islam among through people harsh (Jalal) and some I soft way (Jamal). Although the fragrance of every flower of this garden is different but the objective is only  & only to speared the fragrance of Islam.